Development of a test rig for ceramic-lined steel pipes production by self-propagating high-temperature synthesis (SHS) - Mahmoodian, R. (2009)
The goal of the present research is to develop a test rig for ceramic-lined steel pipes production by self-propagating high-temperature synthesis (SHS) technique or combustion synthesis (CS). SHS is an advanced approach for production high temperature materials including refractory materials, intermetallics, and cermets. SHS process is characterized by extremely fast heating rates, high temperatures, and short reaction times. The products of SHS process are usually porous. Therefore, densification is one step of dense material processing. One of the methods of densification is employing centrifugal force to produce ceramic lined steel pipes and functionally graded materials (FGM). The centrifugal force is the main parameter in combustion of powder reactants and melts formation. It facilitates phase separation of multi-component products during the process. In this research the SHS-centrifugal machine is fabricated to produce ceramic-lined steel pipes from (Fe2O3 +Al) mixture. Fe2O3 and Al powders were mixed based on reaction stoichiometry. The process is based on thermite reaction of Fe2O3 and Al under centrifugal force to produce Al2O3 ceramic in the inner-most layer and molten Fe that diffuses in the steel pipe. The complete combustion reaction was occurred at a distance of 20-30 mm from the head of the pipe to produce two layer ceramic lined steel pipes with a complete phase separation and structure formation. Multilayer phase and structure formation, followed by phase separation occurred in this process. Products were characterized by XRD, SEM, LOM, EDX and micro-hardness. Two and three layers formed inside the steel pipe in various points of the product. Vickers Hardness on the inner-most surface measured reached up to 26 times greater than micro-hardness of a typical pipe. This dissertation includes 8 chapters, 42 figures, 15 tables, 32 references, in 79 pages and appendices.